Critical Evaluation of Disclosure in Annual Reports of Islamic Banks in Bangladesh - Ullah, Md. Hafij; Khanam, Ruma (JABM, 2015)
The present is a critical evaluation of the disclosure practices of the annual reports of Islamic banks in Bangladesh. The study identified 144 disclosure factors required complying by the Islamic banks under traditional and Shari’ah regulations. These factors were classiﬁed into nine including Company Proﬁle Items (CPI) (7), Accounting Policy Items(API) (12), Balance Sheet Items (Assets) (18), Balance Sheet Items (Liabilities) (I 5), Income Statement Items (Cr.) (9), Income Statement Items (Dr.)(11), Ratios, Statistics and Other Details (RSD) (18), Projections and Budgetary Disclosure (PBD) (27) and finally Measurement and Valuation Method (l\/IVM) (27). The study found that on an average,Islamic banks complied the highest 94.28% in case of company profile items and the lowest 38.57% in case of projections and budgetary disclosure. The study suggested giving importance in all the segments of disclosure for quality reporting and disclosing maximum information in their annual report maintaining quality in all the areas as Islam always givesemphasis on full disclosure so that the users of their report can get their required information of the Islamic banks in Bangladesh.